2020
DOI: 10.1136/bmjspcare-2020-002496
|View full text |Cite
|
Sign up to set email alerts
|

‘Supportive and Palliative Care Indicators Tool (SPICT) improves renal nurses’ confidence in recognising patients approaching end of life’

Abstract: BackgroundIdentification of people with deteriorating health is essential for quality patient-centred care and optimal management. The Supportive and Palliative Care Indicators Tool (SPICT) is a guide to identifying people with deteriorating health for care planning without incorporating a prognostic time frame.ObjectivesTo improve renal nursing staff confidence in identifying patients approaching end-of-life and advocate for appropriate multidisciplinary care planning.DesignThis pilot feasibility prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition, three studies found that nurses who were trained to use the SPICT™ increased their self-efficacy in identifying patients who may be nearing the end of life and promoted an advance care plan discussion with these patients 28 29 34 . 21−23 In the study set in a renal ward, patients were screened on admission to identify those nearing the end of life by nurses using the SPICT™ [ 34 ]. An alert was added to the ward patient name list when a patient was identified as nearing the end of life (‘SPICT™ positive’) which prompted a review by the physician and multidisciplinary team.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three studies found that nurses who were trained to use the SPICT™ increased their self-efficacy in identifying patients who may be nearing the end of life and promoted an advance care plan discussion with these patients 28 29 34 . 21−23 In the study set in a renal ward, patients were screened on admission to identify those nearing the end of life by nurses using the SPICT™ [ 34 ]. An alert was added to the ward patient name list when a patient was identified as nearing the end of life (‘SPICT™ positive’) which prompted a review by the physician and multidisciplinary team.…”
Section: Resultsmentioning
confidence: 99%
“…An alert was added to the ward patient name list when a patient was identified as nearing the end of life (‘SPICT™ positive’) which prompted a review by the physician and multidisciplinary team. In this study 16% (25/152) of newly admitted patients were screened as ‘SPICT™ positive’; all of these patients received a palliative care consult and were discharged with an advance care directive including a resuscitation plan [ 34 ]. Incidentally nurses reported a significant increase in their ability to identify patients approaching end of life.…”
Section: Resultsmentioning
confidence: 99%
“…7 These patients had heart/vascular disease, dementia/frailty, and respiratory disease. Renal nurses educated in the use the SPICT identified that 16% of the patients with renal disease required PC 8 Of these patients, 72% died within six months of the study, and these patients had an advance directive. A community-based study in India reported that the SPICT showed that 4.31% of the general population and 20% of individuals with chronic conditions required PC 9 The most common chronic conditions were heart disease (37.5%), dementia/frailty (29.5%), and respiratory diseases (19.3%).…”
Section: Introductionmentioning
confidence: 99%
“…A community-based study in India reported that the SPICT showed that 4.31% of the general population and 20% of individuals with chronic conditions required PC 9 The most common chronic conditions were heart disease (37.5%), dementia/frailty (29.5%), and respiratory diseases (19.3%). Patients with chronic conditions such as liver disease, 10 heart disease, 11 COPD, 12 and renal disease, 8 can benefit from the SPICT because they can then access PC services from health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies show that the tool can be useful as a support in clinical decision-making in hospitals to identify patients in need of palliative care [16] and can be used to identify older hospitalized patients at risk of dying within a year [23]. Furthermore, a study by Lunardi et al 2020 showed [24] that the use of SPICT ™ gave a significant improvement in the nurses' confidence and abilities to recognize patients approaching their end of life.…”
mentioning
confidence: 99%